Bioactive glass 1393 promotes angiogenesis and accelerates wound healing through ROS/P53/MMP9 signaling pathway - Xuenan Chen; Xinyu Ran; Xuebo Wei; Lifei Zhu; Shaodong Chen; Zhiyong Liao; Ke Xu; Weidong Xia (Regenerative Therapy)
Compared to bioactive glass 45S5, bioactive glass 1393 has shown greater potential in activating tissue cells and promoting angiogenesis for bone repair. Nevertheless, the effect of bioactive glass 1393 in the context of wound healing remains extensively unexplored, and its mechanism in wound healing remains unclear. Considering that angiogenesis is a critical stage in wound healing, we hypothesize that bioactive glass 1393 may facilitate wound healing through the stimulation of angiogenesis. To validate this hypothesis and further explore the mechanisms underlying its pro-angiogenic effects, we investigated the impact of bioactive glass 1393 on wound healing angiogenesis through both in vivo and in vitro studies. The research demonstrated that bioactive glass 1393 accelerated wound healing by promoting the formation of granulation, deposition of collagen, and angiogenesis. The results of Western blot analysis and immunofluorescence staining revealed that bioactive glass 1393 up-regulated the expression of angiogenesis-related factors. Additionally, bioactive glass 1393 inhibited the expression of ROS and P53 to promote angiogenesis. Furthermore, bioactive glass 1393 stimulated angiogenesis through the P53 signaling pathway, as evidenced by P53 activation assays. Collectively, these findings indicate that bioactive glass 1393 accelerates wound healing by promoting angiogenesis via the ROS/P53/MMP9 signaling pathway.